Perceived Family Support, Depression, and Suicidal Ideation among People Living with HIV/AIDS: A Cross-Sectional Study in the Kathmandu Valley, Nepal - Amiya, Rachel M.; Poudel, Krishna C.; Poudel-Tandukar, Kalpana; Pandey, Basu D.; Jimba, Masamine (PloS one, 2014)
Depression and suicidal thinking occur frequently alongside HIV/AIDS, triggering profound detrimental impacts on quality of life, treatment adherence, disease progression, and mortality. Yet the psychosocial factors contributing to these psychiatric comorbidities remain underexplored, particularly in the developing country context. This study thus examined different dimensions of perceived family support in relation to depression and suicidal ideation among people living with HIV/AIDS (PLWHA) in Nepal. A cross-sectional survey of 322 adult PLWHA residing in the Kathmandu Valley, Nepal was conducted. Data were analyzed using multiple logistic regressions for correlates of Beck Depression Inventory (BDI)-Ia-defined depressive symptoms and suicidal ideation in the past 2 weeks. Perceived family support, measured using the 10-item Nepali Family Support and Difficulty Scale, was entered into separate models, in turn, as a composite score, for each sub-scale (emotional, instrumental, and negative support), and for each individual item. Overall, 25.5% of participants registered BDI-Ia-defined depression, with significantly lower rates among those with perceived family support scores in the highest (AOR = 0.19; 95% CI = 0.07, 0.55) and middle (AOR = 0.38; 95% CI = 0.17, 0.86) tertiles relative to those with lowest-tertile scores. Meanwhile, 14.0% reported suicidal thinking, with significantly lower rates among those in the highest perceived family support tertile relative to the lowest (AOR = 0.25; 95% CI = 0.07, 0.91). Broken down by support sub-scale, only negative support (i.e. family difficulty) was significant in its correlations with both outcomes - a trend similarly reflected in the item-wise analyses. Our findings highlight an important role for family support in determining experiences of depression and suicidality among PLWHA. Incorporating family counseling and support services - with special focus on ameliorating negative interaction and bolstering emotional support - into HIV care and treatment services may help to improve mental health along with overall wellness and treatment outcomes for HIV-positive populations in Nepal and similar settings.